2021
DOI: 10.3390/diagnostics11091629
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Metal Artifact Reduction Algorithm in Digital Tomosynthesis Using a Combination of Hybrid Generative Adversarial Networks

Abstract: In this study, a novel combination of hybrid generative adversarial networks (GANs) comprising cycle-consistent GAN, pix2pix, and (mask pyramid network) MPN (CGpM-metal artifact reduction [MAR]), was developed using projection data to reduce metal artifacts and the radiation dose during digital tomosynthesis. The CGpM-MAR algorithm was compared with the conventional filtered back projection (FBP) without MAR, FBP with MAR, and convolutional neural network MAR. The MAR rates were compared using the artifact ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Bermudez and other researchers [ 18 ] trained a GAN to synthesize new T1-weighted brain MRIs with high quality compared to that of real images. In the paper by Gomi and others [ 17 ], the authors showed that GAN-based networks could achieve promising results in LDCT denoising. GANs were also used to generate more training data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bermudez and other researchers [ 18 ] trained a GAN to synthesize new T1-weighted brain MRIs with high quality compared to that of real images. In the paper by Gomi and others [ 17 ], the authors showed that GAN-based networks could achieve promising results in LDCT denoising. GANs were also used to generate more training data.…”
Section: Methodsmentioning
confidence: 99%
“…There is an increasing amount of researches on GANs, with each iteration making further progress [ 14 , 15 ]. Due to the excellent performance of GANs on natural image synthesis, GANs were introduced to perform various medical imaging tasks including solving problems associated with data imbalance of virtual STIR images [ 16 ], reducing metal artifacts and the radiation dose during digital tomosynthesis [ 17 ], as well as helping to process medical image [ 18 , 19 ]. Although neural networks and GANs were used to extract strain images from radio frequency data [ 20 , 21 ], and generate shear wave elastography images [ 22 ], we attempted to directly map conventional ultrasound images towards the corresponding strain elastography (SE) images.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent advance in DT is the application of a deep learning program to achieve more advanced metal artifact reduction. Gomi et al reported a novel projection-based cross-domain learning framework for MAR [ 27 ]. They used the novel algorithm and successfully reduced metal artifacts more than with conventional TMAR algorithms.…”
Section: Metal Artifact Reduction Strategiesmentioning
confidence: 99%
“…In the accelerating evolution of deep learning, the transition from a convolutional neural network [ 24 ] to a generative adversarial network (GAN) [ 25 , 26 ] has contributed to digital tomosynthesis imaging [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Prior studies reported that GANs are particularly useful for reducing metal artifacts [ 29 , 30 ] and noise [ 27 ] and are expected to contribute to improvements in image quality processes to reduce the exposure dose. Some studies have recently reported the usefulness of deep learning to improve image quality and reduce noise in tomosynthesis [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have recently reported the usefulness of deep learning to improve image quality and reduce noise in tomosynthesis [ 27 , 29 ]. Noise and radiation-dose reductions using deep learning for digital tomosynthesis of the breast and metal artifact reduction are possible [ 27 , 30 ]. Thus, application of deep learning can be used to improve image quality further and reduce the radiation-dose.…”
Section: Introductionmentioning
confidence: 99%